How We Use Immunohistochemistry to Arrive at a Diagnosis in Breast Lesions - Sahay, Ayushi; Patil, Asawari; Desai, Sangeeta B. (Indian Journal of Medical and Paediatric Oncology, 2022)
Immunohistochemistry (IHC) is an essential tool available to pathologists for facilitating diagnosis and as well as guiding the prognosis of breast lesions. Newer markers are increasingly being added to the pathologists' armamentarium. However, the selection and interpretation of the IHC markers should be judicious. In light of an appropriate morphological assessment, they should complement each other and produce accurate reports. We have briefly outlined here the immunohistochemical approach used in the diagnosis and management of breast cancers at our tertiary care cancer center.
Keywords: immunohistochemistry; breast cancer; biomarker; pathology